Promoção da amamentação durante a hospitalização de recém nascidos: revisão integrativa - Ferrari, Anna Paula [UNESP]; Tonete, Vera Lucia Pamplona [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP] (My University, 2014)
Objective: analyzing interventions to breastfeeding promotion in the neonatal hospitalization. Method: an integrative review from the question << What interventions are appropriate for promotion of breastfeeding during hospitalization of newborns? >>, from the articles published between 2000 and 2012 in English, Portuguese and Spanish, located in LILACS, PubMed/MEDLINE and ScieLO virtual library database. It carried out a descriptive analysis of the data obtained in the 14 articles included in the study, considering the theoretical-methodological and objectives and consistent results. Results: the analysis confirmed the negative influence of neonatal hospitalization for longer lasting breastfeeding, which highlighted the need for comprehensive care and personalized by the interprofessional health care team; favorable hospital environment and family support assured. Conclusion: in addition to encouraging the professional preparation, it is essential that hospitals adopt policies to protect breastfeeding during hospital stay.

Objetivo: analizar las intervenciones para la promoción de la lactancia materna en la hospitalización neonatal. Método: es una revisión integradora de la cuestión << ¿Qué intervenciones son apropiadas para la promoción de la lactancia materna durante la hospitalización de los recién nacidos? >> de artículos publicados entre 2000 y 2012 en Inglés, portugués y español, situado en la base de datos LILACS, PubMed/MEDLINE y SciELO. Se realizó un análisis descriptivo de los datos obtenidos en los 14 artículos incluidos en el estudio, teniendo en cuenta los resultados teórico-metodológicos y de los objetivos y resultados. Resultados: el análisis confirmo la influencia negativa de la hospitalización neonatal para la lactancia materna, que puso de relieve la necesidad de una atención integral y personalizada por el equipo de atención médica interprofesional más duradero; el hospital favorable y el apoyo familiar asegurado. Conclusión: además de fomentar la preparación profesional, es esencial que los hospitales adopten políticas para proteger la lactancia materna durante la estancia hospitalaria.

Objetivo: analisar intervenções para promoção do aleitamento materno na hospitalização neonatal. Método: revisão integrativa a partir da questão << Quais intervenções são adequadas para promoção do AM durante a internação hospitalar de recém-nascidos? >>, de artigos publicados entre 2000 e 2012, em inglês, português e espanhol, localizados nas bases de dados LILACS, Pubmed/MEDLINE e biblioteca virtual Scielo. Procedeu-se análise descritiva dos dados obtidos nos 14 artigos incluídos no estudo, considerando a coerência teóricometodológica e dos objetivos e resultados. Resultados: a análise confirmou a influência negativa da hospitalização neonatal para o aleitamento materno mais duradouro, sendo evidenciada a necessidade de atenção integral e personalizada pela equipe interprofissional de saúde; ambiente hospitalar favorável e apoio familiar assegurado. Conclusão: além do incentivo ao preparo profissional, é imprescindível que os hospitais adotem políticas de proteção à amamentação na vigência da internação.
Promotion of breastfeeding during hospital admission of newly born: an integrative review
Promoción de la lactancia materna durante la hospitalizacion del recien nacido: una revisión integradora
Keywords: Breastfeeding; Hospitalization; Newborn; Health promotion; La lactancia materna; Hospitalización; Recién nacido; Promoción de la salud; Aleitamento materno; Hospitalização; Recém-nascido; Promoção da saúde